FAILED CIVIC ENGAGEMENT: AN EVALUATION OF THE CSA-SIMURP PROGRAMME IMPLEMENTATION IN FARMERS GROUPS FOR CLIMATE CHANGE ADAPTATION - Dwiki Li; Dewi Gunawati; Rima Vien Permata Hartanto (Jurnal Administrasi Publik, 2025)
This research evaluates the effectiveness of the Climate Smart Agriculture–Strategic Irrigation Modernization and Urgent Rehabilitation Project (CSA-SIMURP Programme) in fostering sustainable civic engagement within the Mekar Jaya Farmers Group, Sei Bamban Village, to address climate change. Employing a qualitative case study strategy, the research utilised purposive sampling to select nine subjects, including farmers, management, and government functionaries. Data collection relied on methodological triangulation via semi structured interviews, overt observation, and documentation, with validity confirmed through technical and source triangulation. Qualitative data were analysed inductively using the Coding Colour Analysis Procedure (CCAP), focusing on interpreting power relations through Arnstein’s Ladder of Citizen Participation. The findings confirm that the CSA SIMURP implementation was ineffective, with farmer participation only reaching the level of tokenism rather than genuine citizen power, evidenced by the total regression of CSA practices and institutional deterioration post project. This failure is structurally rooted in the programme's centralistic top down design and feudalistic bureaucratic characteristics, which neglected primary farmer needs and eliminated farmer involvement across all implementation, assistance, and evaluation stages. This systemic approach severed the essential causal link between civic awareness and sustainable civic participation, thereby perpetuating structural dependency. The study concludes that the programme must transition from tokenism to genuine citizen power by revising the technical guidelines to grant farmers negotiation power, integrating infrastructure needs, and reforming the evaluation system to include social outcomes.